65.0k views
5 votes
Consider functions f and g below.

f(x) = -9x^2 - 7x + 12
g(x) = 3x^2 - 4x - 15

Find f(x) - g(x).

A. -12x^2 - 11x - 3
B. 6x^2 - 11x + 27
C. -6x^2 + 3x - 3
D. -12x^2 - 3x + 27

2 Answers

4 votes

Answer:

Option D. -12x² - 3x + 27

Explanation:

The given functions are f(x) = -9x² - 7x + 12 and g(x) = 3x² - 4x - 15

We have to find the value of f(x) - g(x)

f(x) - g(x) = (-9x² - 7x + 12) - (3x² - 4x - 15)

= -9x² - 7x + 12 - 3x² + 4x + 15

= (-9x² - 3x²) - (7x - 4x) + 12 + 15

= -12x² - 3x + 27

This value of f(x) - g(x) matches with option D.

Therefore, Option D. is the correct option.

User Xman Classical
by
7.3k points
3 votes

Answer:

D

Explanation:

f(x) - g(x) = -9x^2 - 7x + 12 - (3x^2 - 4x - 15) Remove the brackets

f(x) - g(x) = -9x^2 - 7x + 12 - 3x^2 + 4x + 15

f(x) - g(x) = -9x^2 - 3x^2 - 7x + 4x + 12 + 15

f(x) - g(x) = -12x^2- 3x + 27

Answer D

User Myuce
by
8.3k points